Shift to Virtual Self-Management Programs During COVID-19: Ensuring Access and Efficacy for Older Adults - Sanchez-Villagomez, Pamela; Zurlini, Claudia; Wimmer, Maggie; Roberts, Linda; Trieu, Bertilia; McGrath, Bonnie; Wiesel, Robyn; Ologhobo, Titilayo; Goldsmith, Sandra; Robbins, Laura (Frontiers in Public Health, 2021)
Background: The COVID-19 pandemic resulted in significant uncertainty and disruption to many aspects of daily living, including physical activity, socialization opportunities and access to healthcare services. Under these conditions, at-risk older adults are even more likely to be inactive and isolated, leading to potential exacerbation of musculoskeletal and chronic conditions and emotional distress. This case study provides an overview of our experience and best practices developed during our shift from onsite programming to virtual. Methodology: HSS utilized varied online approaches, including phone/video conference classes, webinars, on-demand videos and email campaigns to successfully transition programs. Due to this shift, HSS changed its evaluation to an online approach, using a mixed method to adequately assess the impact of programs. Results: Between April and August 2020, our virtual programs reached 339,510 participants, resulting in an 8666% increase in program reach. Most participants assessed were 60 years or older (72%) and reported knowledge (85%) and self-management skills (83%) gained as well as high program satisfaction (90%). Analyses of program data did not show any statistical significant difference in self-reported health outcomes. However, qualitative results showed virtual programming helped to foster social connectivity during COVID-19, helped to build a daily routine, and positively impacted mental and physical health. Conclusion: Shifting to virtual programming in the face of the pandemic enabled us to deliver effective programs affording our community the opportunity to stay physically active and socially connected despite the quarantine orders.